Work-based risk factors and quality of life in health care workers providing maternal and newborn care during the Sierra Leone Ebola epidemic: findings using the WHOQOL-BREF and HSE Management Standards Tool - Nynke van den Broek; Susan Jones; Sarah White; Judith Ormrod; Betty Sam; Florence Bull; Steven Pieh; Somasundari Gopalakrishnan (BMJ Open, 2020)
Introduction Before the 2014, Ebola epidemic in Sierra Leone, healthcare workers (HCWs) faced many challenges. Workload and personal risk of HCWs increased but their experiences of these have not been well explored. HCWs evaluation of their quality of life (QoL) and risk factors for developing work-based stress is important in helping to develop a strong and committed workforce in a resilient health system.Methods Cross-sectional study using World Health Organisation Quality of Life (WHOQOL)-BREF and Health and Safety Executive (HSE) Standards Tools in 13 Emergency Obstetric Care facilities to (1) understand the perceptions of HCWs regarding workplace risk factors for developing stress, (2) evaluate HCWs perceptions of QoL and links to risk factors for workplace stress and (3) assess changes in QoL and risk factors for stress after a stress management programme.Results 222 completed the survey at baseline and 156 at follow-up. At baseline, QoL of HCWs was below international standards in all domains. There was a significant decrease in score for physical health and psychological well-being (mean decrease (95% CI); 2.3 (0.5–4.1) and 2.3 (0.4–4.1)). Lower cadres had significant decreases in scores for physical health and social relationships (13.0 (3.6–22.4) and 14.4 (2.6–26.2)). On HSE peer-support and role understanding scored highly (mean scores 4.0 and 3.7 on HSE), workplace demands were average or high-risk factors (mean score 3.0). There was a significant score reduction in the domains relationships and understanding of role (mean score reduction (95% CI) 0.16 (0.01–0.31) and 0.11 (0.01–0.21)), particularly among lower cadres (0.83 (0.3–1.4).Conclusion HCWs in low-resourced settings may have increased risk factors for developing workplace stress with low QoL indicators; further exploration of this is needed to support staff and develop their contribution to the development of resilient health systems.